УТОЧНЕННЯ ВИЗНАЧЕННЯ МОМЕНТУ АСИНХРОННОГО ДВИГУНА ЗА РЕЖИМІВ МАГНІТОПРОВОДУ У НАСИЧЕНІЙ ОБЛАСТІ - Попович, О.М.; Головань, І.В. (Інститут електродинаміки НАН України, Київ, 2022)
The magnitude of the error in the calculation of the electromagnetic moment is investigated in the operation condition of the magnetic circuit of an induction motor in a saturated region under the assumption that the magnetic energies and сoenergies are equal. For serial motors, in nominal modes, the error does not exceed 5%, with an increase in voltage by 75%, the error increases to 40%. The refined electromagnetic moment is determined by calculating the value of the integral dependences of the magnetic coenergy by the angle of rotation of the rotor, in the process of calculating the dynamic mode of attenuation the currents in the windings. To increase the efficiency of the method of refined calculation of the electromagnetic moment, the dependence of the refinement factor as the function of the motor Magnetic Moving Force (MMF) is proposed. The application of this predetermined dependence significantly speeds up refined calculations. Reasoning of the results reliability of the specified definition of the electromagnetic moment without assumption of equality of magnetic energies and coenergy is carried out by comparison of calculation results of nominal operating conditions of serial motors with two and six poles which have essential discrepancy in saturation degree. References 17, tables 2, figures 2.